Permen Seksi Ratu Ceting (Persiapan Menyusui Asi Ekslusif dengan Sayur Katuk Cegah Stunting pada Ibu Hamil) - Murti Murti; Nurul Hidayah; Elysa Marini; Lisda Handayani (FKIP, Universitas Palangka Raya, 2024)
Breast milk (ASI) is milk produced by mothers and contains nutrients needed by babies for the needs and development of babies. The priority problems that can be drawn from this community service are regarding the preparation and provision of exclusive breastfeeding aimed at pregnant women and women of childbearing age. The solution offered is based on the analysis of the situation and problems that have been explained previously, the author conducted a demonstration of cooking pudding made from local ingredients from katuk vegetables called